Non-Financial Motivation and Job Satisfaction of graduate employees in Hotel industry - Rethinam, Kalaiselvee; Nadarajan, Premkumar; Mohamed, Ramesh Kumar Moona Haji; Nodeson, Suresh; Nodeson, Suresh; Kadiresan, Vimala (International Journal of Psychosocial Rehabilitation, 2020)
Quality and creative hospitality graduates are able to contribute to the country’s economic growth and become the nation’s hope. Focusing on the satisfaction of hospitality graduates through non-financial factors is also very important. Hence, job satisfaction should be taken seriously to produce employees among graduates of quality hospitality. Therefore, the effort to achieve the satisfaction of hospitality graduates needs the cooperation of various parties in the hotel sector, to produce skilled and quality workers. The purpose of this study is to investigate the relationship between the independent variables (promotion, working environment, and employee empowerment) and dependent variable (job satisfaction) while leadership is a moderator. a total of 500 sets of questionnaires are distributed to the graduate hotel employees who work in Penang, Perak, Pahang and Kuala Lumpur only 127 been collected through purposive convenience sampling method. The results reveled that leadership is not play as a moderator role to reduce the job satisfaction through non-financial motivation factor. Its mean there is a non-financial motivation factor that have practices still influencing the employee motivation factor. The limitation and future study have been explained further.